A pure red light perovskite LED, a preparation method and a display screen

CN121152485BActive Publication Date: 2026-10-30HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511140886.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2026-10-30
Estimated Expiration
2045-08-15

AI Technical Summary

Technical Problem

[0003]传统基于III-V族半导体(如InGaP)的红光LED虽具备较高效率,但仍存在显著缺陷:色纯度不足:发光光谱半峰宽(FWHM)通常>35 nm,难以覆盖100% Rec.2020红色色域;波长调控复杂:需精确控制铟镓磷化物组分以实现620-650 nm发射,工艺容错率低;成本与柔性限制:依赖高温外延生长,难以兼容柔性显示和溶液加工技术

Benefits of technology

通过AEBS部分取代OLA配体并垂直锚定在钙钛矿纳米片表面上。直立和刚性的AEBS配体在空间上限制了相邻OLA配体的动态运动,从而抑制了晶格振动并减轻了电子-声子(EP)耦合,促进电荷载流子传输,增强辐射复合,并窄化了发射光谱线宽;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121152485B_ABST
    Figure CN121152485B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of pure red light perovskite LED, comprising: ITO substrate, hole injection layer is arranged on the ITO substrate from bottom to top, hole transport layer, light emitting layer, electron transport layer, electron injection layer and metal cathode, wherein, the light emitting layer is made of perovskite nanosheet, ligand on the perovskite nanosheet is AEBS molecule and OLA ligand.AEBS part is replaced by OLA ligand and vertically anchored on the surface of perovskite nanosheet.Upright and rigid AEBS ligand spatially restricts the dynamic movement of adjacent OLA ligand, thereby inhibiting lattice vibration and reducing electron-phonon (EP) coupling, promoting charge carrier transport, enhancing radiative recombination, and narrowing the emission spectral linewidth;Pure red electroluminescence is realized at 641nm based on AEBS-NPLs PeLED, the linewidth is narrowed to 24 nm, the maximum external quantum efficiency (EQE) is 29.8%, and the working life is 128.2 hours under 100 cdm ‑2 ​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor light-emitting diode technology, and more particularly to a pure red perovskite LED, its preparation method, and a display screen. Background Technology

[0002] With the rapid development of display and lighting technologies, the demand for light-emitting devices with high color purity, high brightness, and high efficiency is increasing. In particular, high color purity red light sources that meet the Rec.2020 color gamut standard have become a core requirement of the industry.

[0003] Traditional red LEDs based on III-V semiconductors (such as InGaP) have high efficiency, but still have significant drawbacks: insufficient color purity: the full width at half maximum (FWHM) of the emission spectrum is usually >35 nm, making it difficult to cover 100% of the Rec.2020 red color gamut; complex wavelength tuning: precise control of the indium gallium phosphide composition is required to achieve 620-650 nm emission, resulting in low process tolerance; cost and flexibility limitations: relying on high-temperature epitaxial growth makes it difficult to be compatible with flexible display and solution processing technologies.

[0004] Metal halide perovskites have attracted widespread attention due to their excellent optoelectronic properties (such as high absorption coefficient, narrow emission linewidth, high carrier mobility, and ease of solution processing), showing great potential in ultra-high-definition display applications. However, achieving efficient and stable pure red PeLEDs, especially PeLEDs with an electroluminescence (EL) linewidth of less than 30 nm at 620-650 nm to meet the Rec.2020 color gamut, remains a key challenge.

[0005] Currently, there are two main strategies for achieving pure red perovskite LEDs: three-dimensional mixed halide (Br / I mixed halide perovskite thin films or nanocrystals) and low-dimensional quantum-confined pure iodine perovskite (nanopieces (NPLs), quantum dots, and quasi-2D thin films). However, existing technologies for pure red perovskite LEDs still face several technical bottlenecks, mainly including the following issues: 1. Wide emission peak width: The electroluminescence (EL) spectral linewidth of existing pure red perovskite LEDs usually exceeds 30nm, which is difficult to meet the Rec.2020 color gamut requirements; 2. Poor stability: Iodine-based perovskites are easily affected by environmental factors (such as humidity, light, heat, etc.) during operation, which leads to a decline in luminescence performance.

[0006] Therefore, developing a pure red PeLED fabrication technology that can synergistically address narrow emission linewidth, high luminous efficiency, and high operational stability has become a key challenge that urgently needs to be overcome in this field. Summary of the Invention

[0007] The present invention aims to provide a pure red perovskite LED, a preparation method, and a display screen to overcome the shortcomings of the prior art. The technical problem to be solved by the present invention is achieved through the following technical solutions.

[0008] According to a first aspect of this application, a pure red perovskite LED is provided, comprising: an ITO substrate, wherein a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a metal cathode are disposed on the ITO substrate from bottom to top, wherein the light-emitting layer is made of perovskite nanosheets, and the ligands on the perovskite nanosheets are AEBS molecules and OLA ligands.

[0009] Preferably, the AEBS molecules are vertically bonded to the surface of the perovskite nanosheets via their own sulfonamide groups.

[0010] Preferably, the hole injection layer is made of PEDOT:PSS material and is used for hole injection; The hole transport layer is made of PTAA material and is used to transport holes; The electron transport layer, made of TPBi material, is used to transport electrons to the light-emitting layer; The electron injection layer is made of lithium fluoride and is used to improve electron injection. The metal cathode is made of aluminum. According to a second aspect of this application, a method for preparing a pure red perovskite LED is provided, comprising the following steps: Step 1: Spin-coat PEDOT:PSS solution onto the pretreated ITO substrate and bake for 20 minutes to complete the preparation of the hole injection layer; Step 2: In a nitrogen atmosphere, spin-coat the PTAA solution onto the hole injection layer, and anneal it to form a hole transport layer; Step 3: After spin-coating the perovskite material onto the hole transport layer, TPBi, lithium fluoride, and aluminum are sequentially deposited under vacuum pressure via thermal evaporation to complete the fabrication of a pure red perovskite LED.

[0011] Preferably, in step 1, the pretreatment of the ITO substrate includes: sequentially washing with deionized water, acetone and isopropanol for 15 minutes each, and then performing oxygen plasma treatment for 15 minutes. After spin-coating the PEDOT:PSS solution, bake at 150°C for 20 minutes.

[0012] Preferably, in step 2, the PTAA concentration in the PTAA solution is 8 mg mL⁻¹, and the solvent is chlorobenzene; after spin coating, the hole transport layer is formed by annealing at 120°C for 20 minutes.

[0013] Preferably, in step 3, the method for preparing the perovskite material includes the following steps: Step 31: Mix 0.26 g zinc iodide, 2.3 mL oleic acid, 1.8 mL LOLA and 6 mL 1-octadecene, then degas under vacuum at 120°C and dry for 30 minutes; Step 32: After cooling to 100℃, inject 1.5ml of precursor solution, cool the mixture to room temperature using an ice-water bath, and obtain perovskite nanosheets after purification; Step 33: Dissolve the perovskite nanosheets and AEBS / SBA-15 nanocomposite material in n-hexane solution, sonicate and centrifuge, collect the supernatant, and filter the supernatant through a 0.22μm polytetrafluoroethylene filter to complete the preparation of perovskite material.

[0014] Preferably, in step 32, the precursor solution is prepared by: Mix 0.21 g cesium carbonate, 0.475 g lead acetate trihydrate, 2.5 mL oleic acid and 10 mL 1-octadecene, and degas under vacuum in an argon atmosphere at 100 °C for 15 minutes. Heat to 120°C and hold for 30 minutes until a transparent solution is obtained, thus completing the preparation of the precursor solution.

[0015] Preferably, in step 33, the preparation method of the AEBS / SBA-15 nanocomposite material is as follows: 50 mg of AEBS powder was dissolved in 10 mL of isopropanol to prepare an AEBS solution; SBA-15 was impregnated in AEBS solution, followed by ultrasonic treatment. The resulting solid product was washed three times with isopropanol. The final AEBS / SBA-15 nanocomposite material was obtained by drying under vacuum conditions.

[0016] According to a third aspect of this application, a display screen is provided that employs the aforementioned pure red perovskite LED.

[0017] The embodiments of the present invention have the following advantages: The AEBS ligands are partially replaced by OLA ligands and vertically anchored on the surface of perovskite nanosheets. The upright and rigid AEBS ligands spatially restrict the dynamic movement of adjacent OLA ligands, thereby suppressing lattice vibrations and mitigating electron-phonon (EP) coupling, promoting charge carrier transport, enhancing radiative recombination, and narrowing the emission spectral linewidth. PeLED based on AEBS-NPLs achieved pure red electroluminescence at 641 nm with a linewidth as narrow as 24 nm. The device has a maximum external quantum efficiency (EQE) of 29.8% and an operating lifetime of 128.2 hours at 100 cd m⁻². Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the structure of a pure red perovskite LED according to the present invention; Figure 2 a is the current density-voltage-luminance (JVL) curve of a pure red perovskite LED; Figure 2 b is the external quantum efficiency-luminosity (EQE-L) curve of a pure red perovskite LED; Figure 2 c represents the EL spectrum of PeLED based on AEBS-NPLs under different driving voltages; Figure 3 PeLED lifetime was measured at an initial brightness of 100 cd m⁻² for a pure red perovskite LED. Detailed Implementation

[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0020] It should be noted that the above detailed descriptions are exemplary and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0021] like Figure 1 As shown, a pure red perovskite LED in one embodiment of this application includes: an ITO substrate, on which a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a metal cathode are disposed from bottom to top. The light-emitting layer is made of perovskite nanosheets, namely CsPbI3 nanosheets (NPLs), and the ligands on the perovskite nanosheets are OLA (oleylamine) long-chain ligands and AEBS (4-(2-aminoethyl)benzenesulfonamide) molecules.

[0022] In this embodiment, the ITO substrate is indium tin oxide with a thickness of 100 nm, and it is made of a conductive and transparent material with a sheet resistance of about 17 Ω sq-1, which serves as the current injection terminal. The hole injection layer is made of PEDOT:PSS material (i.e., poly(3,4-ethylenedioxythiophene):polystyrene sulfonate) and is used for hole injection; The hole transport layer is made of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) material, and is used to selectively transport holes and block electrons; The electron transport layer, made of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (i.e., TPBi) material, is 40 nm thick and is used to transport electrons to the light-emitting layer; The electron injection layer is made of lithium fluoride material with a thickness of 0.8-1nm, which is used to reduce the electron injection barrier of Al electrode, improve electron injection, and protect the underlying organic material. The metal cathode is made of aluminum, which has a high reflectivity (~90%) that can improve light extraction efficiency and has the advantages of low cost and easy vapor deposition.

[0023] In this embodiment, the long-chain oleylamine ligands on the perovskite nanosheets are partially replaced with short-chain 4-(2-aminoethyl)benzenesulfonamide (AEBS) molecules to suppress lattice vibrations and reduce electron-phonon coupling. By introducing shorter and more rigid ligands, the steric hindrance effect is used to reduce the bending and twisting of the long-chain oleylamine ligands, thereby reducing lattice vibrations.

[0024] AEBS molecules are vertically bound to the surface of perovskite nanosheets through their sulfonamide groups (−S(=O)2−NH2), which can enhance the surface passivation of perovskite nanosheets, reduce defect states, stabilize the perovskite structure, and mitigate the degradation of LEDs under bias voltage.

[0025] The vertical binding mechanism of AEBS molecules significantly suppresses electron-phonon coupling in perovskite nanosheets, restricts ligand dynamics, and reduces lattice vibrations.

[0026] The synergistic effect of AEBS molecules suppresses electron-phonon coupling, thereby reducing scattering on the surface of perovskite nanosheets; it also improves carrier mobility, enhancing the injection and recombination of electrons and holes in PeLED devices.

[0027] By introducing novel AEBS ligands to suppress electron-phonon coupling and passivate surface defects in perovskite nanosheets, radiative recombination is increased, thereby improving the external quantum efficiency (EQE) of PeLED.

[0028] The emission linewidth broadening was suppressed by using AEBS ligands in the following ways: reducing lattice vibrations and suppressing electron-phonon coupling of perovskite nanosheets; the pure red PeLED constructed using these perovskite nanosheets achieved a narrow emission linewidth of 24 nm at 641 nm, meeting the full width at half maximum (FWHM) requirement for ultra-high-definition displays.

[0029] AEBS-based ligand exchange enhances the structural stability of perovskite nanosheets and the operational stability of PeLEDs by reducing defect formation and ion migration, and significantly improving operational lifetime.

[0030] This pure red PeLED has the following performance characteristics: a peak EQE of 29.8%; a narrow emission linewidth of 24 nm at 641 nm; and an operating life of 128.2 hours at an initial luminance of 100 cd m⁻², which surpasses the performance limitations of existing technologies.

[0031] According to a second aspect of this application, a method for preparing a pure red perovskite LED is provided, comprising the following steps: Step 1: Spin-coat PEDOT:PSS solution onto the pretreated ITO substrate and bake for 20 minutes to complete the preparation of the hole injection layer; In this step, PeLEDs are fabricated on an ITO-coated glass substrate with a sheet resistance of approximately 17 Ω sq⁻¹. The ITO substrate is pretreated by sequentially washing with deionized water, acetone, and isopropanol for 15 minutes each, followed by oxygen plasma treatment for 15 minutes.

[0032] The poly(ethylene dioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) solution was spin-coated onto an ITO substrate at 4000 rpm and then baked in ambient air at 150°C for 20 minutes to complete the preparation of the hole injection layer.

[0033] Step 2: In a nitrogen atmosphere, spin-coat the PTAA solution onto the hole injection layer, and anneal it to form a hole transport layer; In this step, the ITO substrate is transferred to a nitrogen-filled glove box, and a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] solution (i.e., PTAA solution with a PTAA concentration of 8 mg mL⁻¹ and chlorobenzene as the solvent) is spin-coated onto the PEDOT:PSS layer at 4000 rpm and annealed at 120°C for 20 minutes to complete the preparation of the hole transport layer.

[0034] Step 3: After spin-coating the perovskite material onto the hole transport layer, TPBi, lithium fluoride, and aluminum are sequentially deposited under vacuum pressure via thermal evaporation to complete the fabrication of a pure red perovskite LED.

[0035] In this step, the perovskite material is spin-coated at 2000 rpm for 40 seconds. Subsequently, under a vacuum pressure below 4 × 10⁻⁴ Pa, a 40 nm 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), a 1 nm lithium fluoride (LiF) electrode, and a 100 nm aluminum (Al) electrode are sequentially deposited by thermal evaporation to obtain a perovskite light-emitting diode.

[0036] The preparation method of perovskite materials includes the following steps: First, the precursor was prepared: 0.21 g of cesium carbonate (Cs₂CO₃), 0.475 g of lead acetate trihydrate (Pb(OAc)₂•3H₂O), 2.5 mL of oleic acid (OA), and 10 mL of 1-octadecene (ODE) were added to a 50 mL three-necked flask. The mixture was degassed under vacuum at 100 °C for 15 minutes under an argon atmosphere. Subsequently, the mixture was heated to 120 °C under an argon atmosphere and held for 30 minutes until a clear solution was obtained. The resulting precursor solution was then heated to 100 °C under an argon atmosphere for subsequent injection.

[0037] The next step was the synthesis: 0.26 g of zinc iodide (ZnI2), 2.3 mL of oleic acid (OA), 1.8 mL of oleylamine (OLA), and 6 mL of 1-octadecene (ODE) were added to a 50 mL three-necked flask. The flask was degassed under vacuum at 120 °C and dried for 30 minutes. Subsequently, the temperature was lowered to 100 °C, and 1.5 mL of the precursor solution was rapidly injected. After reacting for 1 minute, the reaction mixture was immediately cooled to room temperature using an ice-water bath.

[0038] Next, the product purification step was performed: the obtained crude product solution was transferred to a 50 mL centrifuge tube, and 15 mL of ethyl acetate was added. The mixture was centrifuged at 10,000 rpm for 5 minutes, and the supernatant was discarded. The precipitate was dissolved in 1 mL of n-hexane, and then 3 mL of ethyl acetate was added. The mixture was centrifuged again at 10,000 rpm for 5 minutes, and the precipitate was collected. The precipitate was dissolved in 1 mL of n-hexane, centrifuged at 5,000 rpm for 3 minutes, and the supernatant was retained. 3 mL of ethyl acetate was added to the supernatant, and the mixture was centrifuged at 10,000 rpm for 5 minutes to separate the precipitate. Finally, the precipitate was redispersed in n-hexane to obtain perovskite nanosheets.

[0039] Finally, ligand post-treatment was performed: 50 mg of 4-(2-aminoethyl)benzenesulfonamide (AEBS) powder was dissolved in 10 mL of isopropanol to prepare an AEBS solution. Mesoporous silica (SBA-15) was added to this solution for impregnation, followed by ultrasonic treatment to promote solution penetration into the mesoporous structure of SBA-15. The resulting solid product was separated, washed three times with isopropanol, and then dried under vacuum to obtain the final AEBS / SBA-15 nanocomposite material.

[0040] Approximately 5 mg of the AEBS / SBA-15 nanocomposite was added to a hexane solution containing perovskite nanosheets. The mixture was sonicated for 3 minutes, followed by centrifugation at 10,000 rpm for 1 minute, and the supernatant was collected. All hexane solutions containing perovskite nanosheets were filtered through a 0.22 μm polytetrafluoroethylene (PTFE) filter.

[0041] In the above steps, the number of each component is increased or decreased synchronously according to the number of perovskite nanosheets required in the desired display screen.

[0042] The performance of the pure red perovskite LEDs prepared using the above steps was tested as follows: the luminescent area was defined as 4 mm². Electroluminescence characterization of the devices was performed at room temperature in a nitrogen-filled glove box using a source meter (Keithley 2400), a 50 mm diameter integrating sphere (manufactured by Shenzhen Spectrum Interconnect Technology Co., Ltd.), and a spectrometer (OceanOptics QE Pro). The operational lifetime of the PeLEDs was evaluated in a nitrogen atmosphere using a commercial organic light-emitting diode aging system (model ZJZCL-1).

[0043] like Figure 2 Current density-voltage-luminance curves (JVL) of PeLED based on AEBS-NPLs; Figure 2 b) External quantum efficiency-luminosity (EQE-L) plot of PeLED based on AEBS-NPLs; and Figure 2 c. EL spectra of AEBS-NPLs-based PeLEDs under different driving voltages. It can be seen that the AEBS-NPLs-based PeLEDs achieved pure red electroluminescence at 641 nm with a linewidth as narrow as 24 nm. Furthermore, these devices exhibit a maximum external quantum efficiency (EQE) of 29.8%.

[0044] like Figure 3 As shown, the PeLED based on AEBS-NPLs had a working life of 128.2 hours when tested at an initial brightness of 100 cd m⁻².

[0045] The embodiments of the present invention have the following advantages: The AEBS ligands are partially replaced by OLA ligands and vertically anchored on the surface of perovskite nanosheets. The upright and rigid AEBS ligands spatially restrict the dynamic movement of adjacent OLA ligands, thereby suppressing lattice vibrations and mitigating electron-phonon (EP) coupling, promoting charge carrier transport, enhancing radiative recombination, and narrowing the emission spectral linewidth. PeLED based on AEBS-NPLs achieved pure red electroluminescence at 641 nm with a linewidth as narrow as 24 nm. The device has a maximum external quantum efficiency (EQE) of 29.8% and an operating lifetime of 128.2 hours at 100 cd m⁻².

[0046] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0047] It should be noted that the terms "first," "second," etc., used in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented in sequences other than those illustrated or described herein.

[0048] Furthermore, the terms “comprising” and “having”, and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product, or apparatus.

[0049] For ease of description, spatial relative terms such as "above," "on top of," "on the upper surface of," "above," etc., are used herein to describe the spatial positional relationship of a device or feature as shown in the figures to other devices or features. It should be understood that spatial relative terms are intended to encompass different orientations in use or operation beyond the orientation of the device as described in the figures. For example, if the device in the figures were inverted, a device described as "above" or "on top of" other devices or structures would subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways, such as rotated 90 degrees or in other orientations, and the spatial relative descriptions used herein will be interpreted accordingly.

[0050] In the detailed description above, reference has been made to the accompanying drawings, which form part of this document. In the drawings, similar symbols typically identify similar parts unless the context otherwise indicates otherwise. The illustrated embodiments described in the detailed specification, drawings, and claims are not intended to be limiting. Other embodiments may be used and other changes may be made without departing from the spirit or scope of the subject matter presented herein.

[0051] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A pure red perovskite LED, characterized in that, include: An ITO substrate is provided with, from bottom to top, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a metal cathode. The light-emitting layer is made of perovskite nanosheets, and the ligands on the perovskite nanosheets are AEBS molecules and OLA ligands. The AEBS molecules partially replace the OLA ligands and are vertically anchored to the surface of the perovskite nanosheets through their own sulfonamide groups. The AEBS molecules spatially restrict the dynamic movement of adjacent OLA ligands to suppress the lattice vibrations of the perovskite nanosheets.

2. The pure red perovskite LED according to claim 1, characterized in that, The hole injection layer is made of PEDOT:PSS material and is used for hole injection; The hole transport layer is made of PTAA material and is used to transport holes; The electron transport layer, made of TPBi material, is used to transport electrons to the light-emitting layer; The electron injection layer is made of lithium fluoride and is used to improve electron injection. The metal cathode is made of aluminum.

3. A method for preparing a pure red perovskite LED, characterized in that, Includes the following steps: Step 1: Spin-coat PEDOT:PSS solution onto the pretreated ITO substrate and bake for 20 minutes to complete the preparation of the hole injection layer; Step 2: In a nitrogen atmosphere, spin-coat the PTAA solution onto the hole injection layer, and anneal it to form a hole transport layer; Step 3: After spin-coating the perovskite material onto the hole transport layer, TPBi, lithium fluoride, and aluminum are sequentially deposited under vacuum pressure by thermal evaporation to complete the preparation of a pure red perovskite LED; wherein, the perovskite material is a perovskite nanosheet with surface ligands including AEBS molecules and OLA ligands, and the AEBS molecules partially replace the OLA ligands and are vertically anchored to the surface of the perovskite nanosheets.

4. The method for preparing a pure red perovskite LED according to claim 3, characterized in that, In step 1, the pretreatment of the ITO substrate includes: sequentially washing with deionized water, acetone and isopropanol for 15 minutes each, and then performing oxygen plasma treatment for 15 minutes. After spin-coating the PEDOT:PSS solution, bake at 150°C for 20 minutes.

5. The method for preparing a pure red perovskite LED according to claim 3, characterized in that, In step 2, the PTAA concentration in the PTAA solution is 8 mg / mL. -1 The solvent is chlorobenzene; after spin coating, the hole transport layer is formed by annealing at 120°C for 20 minutes.

6. The method for preparing a pure red perovskite LED according to claim 3, characterized in that, In step 3, the preparation method of perovskite material includes the following steps: Step 31: Mix 0.26 g zinc iodide, 2.3 mL oleic acid, 1.8 mL OLA and 6 mL 1-octadecene, then degas under vacuum at 120°C and dry for 30 minutes; Step 32: After cooling to 100℃, inject 1.5ml of precursor solution, cool the mixture to room temperature using an ice-water bath, and obtain perovskite nanosheets after purification; Step 33: Dissolve the perovskite nanosheets and AEBS / SBA-15 nanocomposite material in n-hexane solution, sonicate and centrifuge, collect the supernatant, and filter the supernatant through a 0.22μm polytetrafluoroethylene filter to complete the preparation of perovskite material.

7. The method for preparing a pure red perovskite LED according to claim 6, characterized in that, In step 32, the precursor solution is prepared as follows: Mix 0.21 g cesium carbonate, 0.475 g lead acetate trihydrate, 2.5 mL oleic acid and 10 mL 1-octadecene, and degas under vacuum in an argon atmosphere at 100 °C for 15 minutes. Heat to 120°C and hold for 30 minutes until a transparent solution is obtained, thus completing the preparation of the precursor solution.

8. The method for preparing a pure red perovskite LED according to claim 6, characterized in that, In step 33, the preparation method of the AEBS / SBA-15 nanocomposite material is as follows: 50 mg of AEBS powder was dissolved in 10 mL of isopropanol to prepare an AEBS solution; SBA-15 was impregnated in AEBS solution, followed by ultrasonic treatment. The resulting solid product was washed three times with isopropanol. The final AEBS / SBA-15 nanocomposite material was obtained by drying under vacuum conditions.

9. A display screen, characterized in that, The pure red perovskite LED described in claim 1 or 2 is used.

Citation Information

Patent Citations

  • Perovskite solar cell and preparation method thereof

    CN117156877A

  • Preparation method and application of surface passivation red light perovskite quantum dots

    CN120209835A